2021
DOI: 10.1002/slct.202004721
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Electronic Energy Transfer and Reversible Photoreactions in a Triad Comprising Two Different Styrylbenzoquinoline Photochromes and a ′Hidden′ Quencher

Abstract: A trichromophoric triad comprising two different 3-styrylbenzo [f]quinoline photochromes (SBQ1 and SBQ2) and a residue of 3oxy-2-naphthoic acid (NA) was synthesized and studied by steady-state and time-resolved spectroscopy and by DFT calculations. The SBQ photochromes are linked to the NA framework by methylene spacers of different lengths to provide a longitudinal displacement between the photochromes. Under light irradiation, the triad undergoes two competitive reactions, intra-photochrome photoisomerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…These maxima are characteristic of the benzoquinoline core and indicate a break of the SBQ π-conjugated system. Taking into account an analogy in properties of the dyad D44B and previously studied supramolecular systems with the SBQ photochromes, 22–25 the final spectrum 10 in Fig. 4 can be attributed to the cyclobutane CB44B , which forms from the dyad D44B as a result of the PCA reaction, Scheme 4.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…These maxima are characteristic of the benzoquinoline core and indicate a break of the SBQ π-conjugated system. Taking into account an analogy in properties of the dyad D44B and previously studied supramolecular systems with the SBQ photochromes, 22–25 the final spectrum 10 in Fig. 4 can be attributed to the cyclobutane CB44B , which forms from the dyad D44B as a result of the PCA reaction, Scheme 4.…”
Section: Resultsmentioning
confidence: 76%
“…We have recently found that supramolecular systems, dyads and triads, with covalently linked styrylbenzoquinoline (SBQ) photochromes are suitable objects for studying the PCA reaction. 20–24 Using a balanced rigid-flexible linker between SBQ units, we observed for the first time both emissive and reactive excimers in the PCA reaction. 25…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations